Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Toko Rendy Cell Cabang Gunung Pangilun Menggunakan Metode MFEP (Multi Factor Evaluation Process) - Sisi Andali; Nia Anggraini; Diah Agustrian; Fira Anjelina; Livia Agustin; Hendra Hendra; Irsyadunas Irsyadunas (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
The purpose of this study is to produce a Decision Support System for Employee Performance Assessment Using the Multifactor Evaluation Process (MFEP) Method. At the Rendi cell store, the Gunung Pangilun branch in the hope of encouraging employees to be enthusiastic about working using the Visual Basic programming language and databases using Microsoft Access. In this study, the data collection techniques used were field studies, observation, interviews and decision studies. The Best Employee Selection Decision Support System, is a system created to assist in making decisions in selecting the best employees at the Rendi cell store at the Gunung Pangilun branch by using the Multi Factor Evaluation Process (MFEP) method. The result of this research is a decision support system is made to find out the best employees based on the results of employee performance appraisals. Users can input employee data, employee assessment data for each factor, then the system will find a solution using the (MFEP) method. After the decision is obtained, the system will display the decision.